Introduction - Jo Mynard (Studies in Self-Access Learning Journal)
Welcome to the September 2023 issue of SiSAL journal, which contains four papers in the main section, three papers in the Ethnographies of Self-Access section, and two reviews (edited by Hisako Yamashita). Contributors are based in Japan, Malaysia, the Philippines, Turkey and Vietnam.